(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Inorder to assess the role of FDI on economic growth, two models were used. Theestimation results of the two models are supported and further analysed byusing the elevant econometric techniques viz. Coefficient of determination,standard error, f- ratio, - statistics, D-W Statistics etc. In the foreigndirect investment model , the main determinants of FDI inflows to India areassessed. The study identified the following macroeconomic variables: TradeGDP,R&DGDP,